Mathematics and Design Education. - Özcan, Oğuzhan; Akarun, Lale (Design Issues)
Focuses on the application of mathematics course in the multimedia design program. Information on the Topdown Programming Shell; Information on the book 'Design By Number,' by John Maeda; Mathematics instruction in design education; Topics and subjects covered in the course.